IMPLEMENTASI PROGRAM SENTRA HORTIKULTURA DI DESA WULURMAATUS KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - RENALDY EDDY PRANG; FEMMY TULUSAN; VERY LONDA (JURNAL ADMINISTRASI PUBLIK, 2022)
This research was conducted to determine the implementation of the horticulture center program in Wulurmaatus Village, Modoinding District, South Minahasa Regency. By using qualitative research methods. Efforts or programs from the government in implementing horticulture centers in Wulurmaatus village are realized through several programs for the community who are members of farmer groups such as fertilizer assistance, agricultural tools, education and training and assistance of superior seeds. However, it was found that the implementation of these programs had not run optimally, several obstacles hindering the running of the horticulture center program in Wulurmaatus Village, including the uneven socialization of the horticulture center program and the lack of discipline of implementing agencies in Modoinding sub-district, which is very influential. to the welfare of the people in the village of Wulurmaatus. Keywords: Implementation, Program, Center, Horticulture.